Effect of the first thermal stage temperature and retention time in two-stage thermal upgrading of low-grade nickel lateritic ore. (February 2019) - Shofi, A; Ramadini, C; Samuel, R; Nurjaman, F; Suharno, B; Subagja, R
Abstract: Selective reduction process and magnetic separation of nickel lateritic ore wereconducted through the two-stage thermal upgrading processwith the addition of sodium sulphate and sodium chloride as the additives agent. Effect of the first thermal stage temperature has been investigated at various of temperature of 500, 600 and 700°C for 60 minutes and continued with the reduction process at temperature of 1050°C for 30 minutes. The mineralogical composition of the reduced samples was performed by XRD analysis. The optimum temperature was 500°C, which produced a concentrate withnickel grade of 2.98% and iron recovery of 40.17%. Effect of the first thermal stageretention time also has been investigated at temperature of 500°C for 30, 60, and 90 minutes, and continued with the reduction process at temperature of 1150°C for 60 minutes. The optimum temperature was 90 minutes, which produced a concentrate with 3.69% nickel grade, and 90.61% nickel recovery.